EFFECT OF ORGANIC ZINC SUPPLEMENTATION ON PERFORMANCE, BIOCHEMICAL PARAMETERS AND DEPOSITION OF ZINC IN EGGS IN WHITE LEGHORN LAYERS - A.K.PANDA, K. APPALASURI, K. VIJAYA LAKSHMI, N. NALINI KUMARI, D. KRISHNA and (The Journal of Research, PJTSAU, 2019)
An experiment was conducted with an aim to study the effect of organic Zn supplementation on performance, egg quality parameters, biochemical parameters and retention of Zinc in White Leghorn layers. One forty four layers at thirty eight weeks age were randomly allotted to 144 replicates considering each bird as a replicate. The hens were reared in individual California type cages having the provision of individual feeding. A corn-soybean meal, deoiled ricebran basal diet (BD) was prepared for layers to meet the nutritional requirements, as recommended by NRC (1994) except Zn. Experimental diets were viz., BD with 35 ppm Zn supplementation from ZnSO4 (inorganic) and BD with Zn- bioplex (organic) at 35, 70 and 105 ppm. Each diet was allotted to 36 replicates and fed ad libitum from 38 to 50 weeks of age. Body weights, feed intake and feed conversion ratio (FCR) were measured period wise. At the end of each 28 days period, eggs were collected during the last 5 days from all the birds to record egg weight and egg quality parameters. The Zn content in egg was measured using Atomic Absorption Spectrophotometry. At the last week of feeding trial, blood samples were collected from 8 birds of each dietary treatment to collect serum and measure total protein. Increasing the concentration of organic Zn from 35 ppm to either 70 or 105 ppm in diet had no further advantage on feed intake, FCR, hen day egg production, egg weight, body weight gain, egg quality parameters and serum Ca and P values significantly (P>0.05). However, serum total protein concentration was significantly (P